Masala Bond Program–Nurturing a Local Currency Bond Market - Shi, Lin (International Finance Corporation, Washington, DC, 2018)
The financing needs of emerging markets are enormous. Sectors such as infrastructure, small business, and housing are vital to a nation’s sustainable development and require substantial financing support. Since these sectors primarily generate revenues in local currency, foreign currency financing may incur a mismatch that can expose emerging market borrowers to exchange rate risk in times of high volatility. Local currency bond issuance is a significant potential option that avoids such risks and can support private sector investment in productive sectors of emerging markets.